2017
DOI: 10.1002/wrna.1435
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin‐associated noncoding RNAs in development and inheritance

Abstract: Noncoding RNAs (ncRNAs) have emerged as crucial players in chromatin regulation. Their diversity allows them to partake in the regulation of numerous cellular processes across species. During development, long and short ncRNAs act in conjunction with each other where long ncRNAs (lncRNAs) are best understood in establishing appropriate gene expression patterns, while short ncRNAs (sRNAs) are known to establish constitutive heterochromatin and suppress mobile elements. Additionally, increasing evidence demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 227 publications
0
4
0
Order By: Relevance
“…The co-expression and co-localization relationship of “LNC_000285– baz2a ” indicated that the lncRNA LNC_000285 probably mediated the regulatory effects of dietary DHA/EPA on gene expression through promoting heterochromatin formation. Inducing heterochromatin formation and suppressing mobile elements were major mechanisms of transcription-regulating effects of non-coding RNAs (Cusanelli and Chartrand, 2015; Meller et al, 2015; Acharya et al, 2017; da Rocha and Heard, 2017; Oliva-Rico and Herrera, 2017). In human pancreatic ductal adenocarcinoma, the lncRNA HOTAIR contributed in the silence of MicroRNA-34a by enchancer of zeste homolog 2 through induction of heterochromatin formation (Li et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The co-expression and co-localization relationship of “LNC_000285– baz2a ” indicated that the lncRNA LNC_000285 probably mediated the regulatory effects of dietary DHA/EPA on gene expression through promoting heterochromatin formation. Inducing heterochromatin formation and suppressing mobile elements were major mechanisms of transcription-regulating effects of non-coding RNAs (Cusanelli and Chartrand, 2015; Meller et al, 2015; Acharya et al, 2017; da Rocha and Heard, 2017; Oliva-Rico and Herrera, 2017). In human pancreatic ductal adenocarcinoma, the lncRNA HOTAIR contributed in the silence of MicroRNA-34a by enchancer of zeste homolog 2 through induction of heterochromatin formation (Li et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The X-inactivation center (XIC) that can be transcribed to lncRNA Xist is essential and necessary during inactivation [58]. Previous studies have shown that many Xist RNAs might coat the X-chromosome in cis, consequently interacting with approximately 1000 genes directly and leading to transcriptional repression [59]. However, the latest research suggests that interaction with only approximately 50 locally confined foci on the inactive X-chromosome by approximately 100 Xist RNAs which trigger more than 1000 genes to become inactive [60].…”
Section: Chromatin-associated Noncoding Rnas Have Significant Functio...mentioning
confidence: 99%
“…lncRNA-directed processes also function in dosage compensation in Drosophila, where the localization of the histone acetyltransferase MOF to the male X chromosome is dependent on roX ncRNAs [ 15 ]. Moreover, recent findings suggest that ncRNAs are integral components of chromatin [ 12 , 13 ] that play an important role in the higher-order chromatin structure of pericentric heterochromatin by organizing heterochromatic components [ 16 , 17 ]. In plants, lncRNAs have been reported to interact with chromatin remodelers [ 18 ].…”
Section: Introductionmentioning
confidence: 99%